2015
DOI: 10.1080/02692171.2014.945991
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the relationship between domestic investment and foreign aid: does political stability matter?

Abstract: While past studies had conflicting conclusions regarding the impact of foreign aid on growth and development of a nation, recent studies have tried to delve deeper into the question, 'what makes aid work?' (see, Dutta, Leeson, and Williamson, 2013; Dollar, 2000, 2004;Svensson, 1999). This paper tests how political stability (vis-à-vis political instability) affects the relationship between domestic investment and foreign aid. Applying dynamic panel estimators, our results show that political stability affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
3
0
2
Order By: Relevance
“…While the average positive impact of aid on growth is fairly recognized, the contrasting view that the positive impact of aid on growth depends on certain conditions or good policies in recipient countries should not be ignored. The aid conditionality argument is believed to be fairly propagated by Burnside and Dollar (2000) and subsequent studies (Alvi et al, 2008;Dutta et al, 2015). Burnside and Dollar (2000) tested the aid conditionality hypothesis using panel data form 56 major aid-recipient countries over the 1970-1993 period.…”
Section: Aid Positively Affects Growth Only Under Certain Conditions:...mentioning
confidence: 99%
See 2 more Smart Citations
“…While the average positive impact of aid on growth is fairly recognized, the contrasting view that the positive impact of aid on growth depends on certain conditions or good policies in recipient countries should not be ignored. The aid conditionality argument is believed to be fairly propagated by Burnside and Dollar (2000) and subsequent studies (Alvi et al, 2008;Dutta et al, 2015). Burnside and Dollar (2000) tested the aid conditionality hypothesis using panel data form 56 major aid-recipient countries over the 1970-1993 period.…”
Section: Aid Positively Affects Growth Only Under Certain Conditions:...mentioning
confidence: 99%
“…Furthermore, a strand of literature has shown that aid works differently across different circumstances. These include studies that found: first, the positive effect of aid on growth differs across countries with aid exhibiting diminishing returns at higher level due to 'timing aid effect' and types of aid (Clemens et al, 2012;Doucouliagos and Paldam, 2010;Dutta et al, 2015). Second, the effect of aid on growth differs when disaggregating the sample into different regions/sub-regions where aid has a significant positive impact on growth in Africa but not in Asia, Latin America and the Caribbean (Ekanayake and Chatrna, 2010).…”
Section: The Link Between Aid and Growth: Review Of Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Tandis que les études de régression sur la croissance au sens large ont mis en doute l'efficacité de l'aide aux pays émergents (par exemple Rajan et Subramanian, 2008), les nouvelles stratégies de répartition de l'aide des bailleurs de fonds produisent des résultats positifs dans certains cas. L'aide étrangère peut stimuler les transferts de technologie et la productivité dans les pays à faible revenu par différents canaux : (Burnside et Dollar, 2000 ;Collier et Dollar, 2002 ;Dutta, Mukherjee et Roy, 2015).…”
Section: Vérifier Le Rôle De L'acquisition De Technologie Comme Canal...unclassified
“…Исследования показали, что на макроэкономическом уровне иностранная помощь может способствовать передаче технологий и повышению производительности в странах с низкими доходами. Например, в работе Walley and Cushing (2013) (Burnside and Dollar, 2000;Collier and Dollar, 2002;Dutta, Mukherjee, and Roy, 2015).…”
Section: проверка роли использования внешних технологий в качестве ка...unclassified